Resonant and scattering exceptional points in non-Hermitian metasurfaces - Yifan Shou; Dong Wang; Yanxiang Wang; Qiang-Kai-Lai Huang; Hanqi Chen; Wenduo Yu; Ran Ju; Hongsheng Chen; Ying Li (npj Nanophotonics)
Abstract Exceptional points (EPs), as unique singularities in non-Hermitian systems, can trigger distinctive effects in open quantum systems. This review proposes a systematic framework to analyze EP characteristics in non-Hermitian metasurfaces. Starting from the foundational theory of parity-time symmetry, we classify EPs into two categories—resonant EPs and scattering EPs—based on distinct analytical perspectives. Through case studies of typical applications, we clarify the practical scenarios of both EP types in photonic devices and reveal their fundamental differences. Although both exhibit coalescence of eigenvalues and eigenstates, their physical nature requires interpretation through different theoretical models. We demonstrate that both EP categories encode critical information of the system’s Hamiltonian and can establish their intrinsic connections via topological property analysis. The proposed framework contributes to the theoretical analysis of non-Hermitian metasurfaces while exploring practical approaches for EP control in photonic systems, which may offer useful insights for future EP metasurface designs.